Massage for sport - Watt, Joan (The Crowood Press, 1999)
In this book, physiotherapist Joan Watt addresses the rules of sports massage and its techniques. She covers techniques, contact materials, methods of application, duration, and contra-indications, as well as ice massage, aromatherapy and reflexology as additions to the masseur's skills.